The Effect Of Service Quality, Taxpayer Satisfaction And Tax Penalty On Individual Taxpayer Compliance - Az Zahra, Aqilah; Mahpudin, Endang (Peneliti.net, 2023)
The purpose of this study was to determine the effect of service quality, taxpayer satisfaction and tax penalty on individual taxpayer compliance. This research was conducted in Karawang in 2023. This research used a quantitative approach. Samples taken by purposive sampling technique, with a total sample of 100 respondents. Methods of data collection related to research using a questionnaire method in the form of a statement. The results of the partial test (t) show that Service Quality, Taxpayer Satisfaction and Tax Penalty have an effect on Individual Taxpayer Compliance. The results of the simultaneous test (f) show that the independent variables have a joint effect on the dependent variable The purpose of this study was to determine the effect of service quality, taxpayer satisfaction and tax penalty on individual taxpayer compliance. This research was conducted in Karawang in 2023. This research used a quantitative approach. Samples taken by purposive sampling technique, with a total sample of 100 respondents. Methods of data collection related to research using a questionnaire method in the form of a statement. The results of the partial test (t) show that Service Quality, Taxpayer Satisfaction and Tax Penalty have an effect on Individual Taxpayer Compliance. The results of the simultaneous test (f) show that the independent variables have a joint effect on the dependent variable.